Generation and usage of aequorin lentiviral vectors for Ca2+ measurement in sub-cellular compartments of hard-to-transfect cells. Issue 5 (May 2016) - Lim, Dmitry; Bertoli, Alessandro; Sorgato, M.Catia; Moccia, Francesco
Graphical abstract: Highlights: Bioluminescent sensors are used in laboratory, industrial and clinical applications. Targeted aequorin is a tool of choice to measure [Ca 2+ ] in subcellular compartments. Lentiviral aequorin vectors are useful to measure [Ca 2+ ] in hard-to-transfect cells. We describe strategies for the generation of lentiviral aequorin Ca 2+ probes. Subcellular Ca 2+ signals were measured by this approach in hard-to-transfect cells Abstract: Targeted aequorin-based Ca 2+ probes represent an unprecedented tool for the reliable measurement of Ca 2+ concentration and dynamics in different sub-cellular compartments. The main advantages of aequorin are its proteinaceous nature, which allows attachment of a signal peptide for targeting aequorin to virtually any sub-cellular compartment; its low Ca 2+ -binding capacity; the wide range of Ca 2+ concentrations that can be measured, ranging from sub-micromolar to millimolar; its robust performance in aggressive environments, e.g., the strong acidic pH of the lysosomal lumen. Lentiviral vectors represent a popular tool to transduce post-mitotic or hard-to-transfect cells both in vitro and in vivo . Furthermore, it has great potential for gene therapy. Last generation lentiviral vectors represent a perfect compromise for combining large insert size, ease of production and handling, and high degree of biosafety. Here, we describe strategies for cloning aequorin probes – targeted to the cytosol, sub-plasma membrane cytosolic domains, the mitochondrial matrix, and the endoplasmic reticulum lumen – into lentiviral vectors. We describe methods for the production of lentiviral particles, and provide examples of measuring Ca 2+ dynamics by such aequorin-encoding lentiviral vectors in sub-cellular compartments of hard-to-transfect cells, including immortalized striatal neurons, primary cerebellar granule neurons and endothelial progenitor cells, which provide suitable in vitro models for the study of different human diseases.